Entrenamiento de habilidades sociales en contextos vulnerables para mejorar la convivencia (2019)
In this research work, pedagogical strategies were developed for the strengthening of social skills in students in vulnerable contexts to improve coexistence in the students of grade 3 B of the Industrial Technical Educational Institution María Auxiliadora - Headquarters 1. The research began with a Pre Test applied to students which allowed to identify the level of social skills to a sample of 33 students. Subsequently, a training plan based on primary social skills for students was developed, including the inclusion of strategies, didactic and recreational, during an academic semester. After the application of the training plan, a Post Test evaluation was applied to the students, with the purpose of comparing their degree of development in the students. The study showed that the 33 students after having developed strategies and didactics in topics related to social skills showed an increase in the strengthening of these. It was concluded that the implementation of a training plan for the strengthening of social skills contributes to their development, if the program has innovative pedagogical strategies.